PERDAGANGAN PAKAIAN SECOND BRANDED DARI SINGAPURA KE BATAM DALAM KERANGKA MASYARAKAT EKONOMI ASEAN TAHUN 2015-2016 - Suwandoko, Nurul; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describe the second branded clothes bussiness from Singapore to Indonesia in Asean Economic Community in 2015-2016. Regionalism are one of agreement between states to create a marekt brief in regions. Asean Economic community was held since 2015 to anticipation the trade from China and India and it’s make a common market in South East Asia Regions.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Government of Indonesia implemented export constant price for cocoa product from Indonesia to China. The theories applied in this research are neo liberalism with globalization concept.The result shows that the second branded clothes bussiness from Singapore to Indonesia in Asean Economic Community in 2015-2016 are was increase and it’s make effect teh disadvantage for locall textile production. Dsince 2015 the second branded from Singapore was enterance in Batam Island by illegal harbour and the Indonesia government by Custom instituitons was checking the second branded from Singapore.Key words: bussiness, second branded and MEA.